Effect of Huangqin Tang on Colonic Gene Expression in Rats with Ulcerative Colitis - Wang, Dunfang (Int J Genomics, 2020)
In this study, we explored the pharmacological mechanisms of Huangqin Tang (HQT; a traditional Chinese medicine formula) in ulcerative colitis (UC) and provided evidence for potential roles HQT plays by gene expression profiling. The UC rat model was made via a compound method (trinitrobenzene sulfonic acid plus ethanol). After a ten-day treatment, microarray analysis was performed from the colon segment of the rats. Biological functions and specific signaling pathways were enriched based on differentially expressed genes (DEG), and corresponding gene networks were constructed via Ingenuity Pathway Analysis (IPA). Through the network, we screened the potential “candidate targets,” such as ITGB1, FN1, CASP3, and ITGA5 and FABP1, ABCB1, FABP2, and SLC51B. These potential candidate targets were functionally related to immune responses, inflammation, and metabolism. Moreover, HQT significantly decreased serum levels of proinflammatory factors nitrogen monoxide (NO), proinflammatory cytokines interleukin- (IL-) 17, and prostaglandin E2 (PGE2). The degree of HE staining of colonic tissue was severe in the model group but reduced significantly in the HQT group. HQT exhibited protective effects against colon damage by inhibiting the inflammatory response.